Bronze age barrow and Anglo-Saxon cemetery : archaeological excavations on land adjacent to Upthorpe Road, Stanton, Suffolk : November 2013-March 2014 - Chinnock, Chris (Archaeopress Archaeology, 2023)
Revealing the remains of a prehistoric round barrow and a cemetery containing the remains of 67 inhumations with associated grave goods, this book provides detailed analysis of the archaeological features, skeletal assemblage and other artefacts.